KEANEKARAGAMAN JENIS RAYAP DI LAHAN GAMBUT TERBUKA PADA BERBAGAI TINGGI MUKA AIR DESA KUALA DUA KABUPATEN KUBU RAYA - Sitorus, Yopa Sandra; Astiani, Dwi; Ekyastuti, Wiwik (Universitas Tanjungpura, 2018)
The purpose of this study is to obtain data on the diversity of termite species found in peatland at using on various water table levels. The method used in this research is survey, transect method with plot based on water level of 30, 40, 50 and 60 cm which previously been established in the field. The plots were made parallel to the ditch with a distance of Â± 2 m from the transect. The size of one plot was 100 m x 2 m and made into 20 plots with the size of 5 m x 2 m so that the total of all plots is 80 plot. In each plot, the observation and searching of termites manually by digging the soil as deep as Â± 20 cm. Termite criteria sampled were caste soldiers termite with red head trait and taken as much as 5-10 termites. Sampling of termites should be done for one hour per one observation plot. The termite samples obtained are then inserted into glass vials containing alcohol and further identification was done in the laboratory. The study found 3 species of termites namely Coptotermes curvignathus, Schedorhinotermes sarawakensis and Schedorhinotermes medioobcurus from sub families Coptotermitinae and Rhinotermitinae.Keywords: Identification, termite, water table levels